Phosphorylation of the Amyloid-Beta Peptide Inhibits Zinc-Dependent Aggregation, Prevents Na,K-ATPase Inhibition, and Reduces Cerebral Plaque Deposition - Barykin, Evgeny P.; Petrushanko, Irina Y.; Kozin, Sergey A.; Telegin, Georgy B.; Chernov, Alexander S.; Lopina, Olga D.; Radko, Sergey P.; Mitkevich, Vladimir A.; Makarov, Alexander A. (Frontiers in Molecular Neuroscience, 2018)
The triggers of late-onset sporadic Alzheimer’s disease (AD) are still poorly understood. Impairment of protein phosphorylation with age is well-known; however, the role of the phosphorylation in β-amyloid peptide (Aβ) is not studied sufficiently. Zinc-induced oligomerization of Aβ represents a potential seeding mechanism for the formation of neurotoxic Aβ oligomers and aggregates. Phosphorylation of A by Ser8 (pS8-Aβ), localized inside the zinc-binding domain of the peptide, may significantly alter its zinc-induced oligomerization. Indeed, using dynamic light scattering (DLC), we have shown that phosphorylation by Ser8 dramatically reduces zinc-induced aggregation of A, and moreover pS8-Aβ suppresses zinc-driven aggregation of non-modified Aβ in an equimolar mixture. We have further analyzed the effect of pS8-Aβ on the progression of cerebral amyloidosis with serial intravenous injections of the peptide in APPSwe/PSEN1dE9 murine model of AD, followed by histological analysis of amyloid burden in hippocampus. Unlike the non-modified Aβ that has no influence on the amyloidosis progression in murine models of AD, pS8-Aβ injections reduced the number of amyloid plaques in the hippocampus of mice by one-third. Recently shown inhibition of Na+,K+-ATPase activity by Aβ, which is thought to be a major contributor to neuronal dysfunction in AD, is completely reversed by phosphorylation of the peptide. Thus, several AD-associated pathogenic properties of Aβ are neutralized by its phosphorylation.